Well-isolated pyrazine-bridged copper(II) chains: synthesis and magneto-structural analysis. Issue 17 (9th July 2020) - Monroe, Jeffrey C.; Landee, Christopher P.; Turnbull, Mark M.; Wikaira, Jan L.
Abstract: A pair of well-isolated 1-D-QHAF compounds with the molecular formula [Cu(pz)(L)2 (H2 O)2 ](ClO4 )2 with L = 3-Cl-4-hydroxypyridine (1 ) and 3-Br-4-hydroxypyridine (2 ) ( catena-(diaqua-bis(3-chloro/bromo-4-pyridono-κO)(μ-pyrazine)copper(II) diperchlorate ) were synthesized via slow-evaporation crystallization and characterized structurally and magnetically to develop magneto-structural correlations. Single-crystal X-ray diffraction at 120 K provided the structures of 1 and 2 which comprise six-coordinate Cu(II) pyrazine-bridged chains propagating parallel to the crystallographic a -axis in the triclinic space-group P -1. Chains are offset from each other in the c -direction by the bulk of L and along the dz2 axis occupied by a semi-coordinate water molecule engaged in hydrogen bonding with the perchlorate gegenion. Magnetic susceptibility experiments showed that 1 and 2 behave as quasi-Heisenberg 1-D-AFMs with J ≈ 8 K and no sign of 3 D ordering down to 1.8 K. Aspects of crystal engineering are addressed to understand the potential to design systems with desired magnetic properties in light of comparisons with a variety of pyrazine-bridged chains already in the literature. The effect of L and the general structural scaffold are investigated to this end. Powder X-Band EPR experiments were performed to determine the electronic environment of the Cu(II) ion and average g-factor. The pyrazine-bridged chains in 1 with the AFM electronic spins represented as glowing arrows. Graphical Abstract: